Wage Discrimination Against Immigrants in Austria?. (18th April 2017) - Hofer, Helmut; Titelbach, Gerlinde; Winter‐Ebmer, Rudolf; Ahammer, Alexander
Abstract: This paper analyses wage discrimination against immigrants in Austria using combined information from the labour force surveys and administrative social security data. We find that immigrants experience a wage penalty of 15 percentage points compared with natives. However, a substantial part of this gap can be explained by differences in human capital endowment and job position. Decomposition methods using quantile regressions indicate larger discrimination in the upper part of the wage distribution.